2005
DOI: 10.4049/jimmunol.175.5.3235
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Granzyme M and Its Role in Immunity to Infection

Abstract: Cytotoxic lymphocytes express a large family of granule serine proteases, including one member, granzyme (Grz)M, with a unique protease activity, restricted expression, and distinct gene locus. Although a number of Grzs, including GrzM, have been shown to mediate target cell apoptosis in the presence of perforin, the biological activity of Grz has been restricted to control of a number of viral pathogens, including two natural mouse pathogens, ectromelia, and murine CMV (MCMV). In this article, we describe the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 46 publications
4
58
0
1
Order By: Relevance
“…GrM knockout mice are more susceptible to MCMV infections, indicating a role of GrM in CMV clearance at least in mice. 18 If GrM has a major role in controlling HCMV infections in humans, one would expect that GrM is present in HCMVspecific cytotoxic lymphocytes. Therefore, we analyzed GrM expression in CD8 þ T cells of healthy human HCMV-seropositive individuals as well as in seronegative renal transplant recipients receiving a kidney from an HCMV-seropositive donor, followed by primary HCMV infections.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…GrM knockout mice are more susceptible to MCMV infections, indicating a role of GrM in CMV clearance at least in mice. 18 If GrM has a major role in controlling HCMV infections in humans, one would expect that GrM is present in HCMVspecific cytotoxic lymphocytes. Therefore, we analyzed GrM expression in CD8 þ T cells of healthy human HCMV-seropositive individuals as well as in seronegative renal transplant recipients receiving a kidney from an HCMV-seropositive donor, followed by primary HCMV infections.…”
Section: Resultsmentioning
confidence: 99%
“…The physiological importance of GrM as an antiviral mediator has been demonstrated in GrM-deficient mice, which are more susceptible to MCMV infections. 18 However, both murine GrM and MCMV have been largely diverged from their human counterparts, 1,21 emphasizing that caution is essential when extrapolating data from mice to humans. In this study, we demonstrated for the first time that human GrM is expressed in HCMV-specific CD8 þ T cells after primary infection and during latency (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, granzyme M-deficient mice have recently been generated, and although NK cells from these animals showed no cytotoxic defect, a delay in the clearance of MCMV suggests that granzyme M may play a role in the eradication of some viral infections. 154 With regard to the tumorigenic function of CTL/NK cells, granzyme deficiency has produced conflicting results and, to date, an increased susceptibility of granzyme B-deficient mice to lymphoma has not been reported. In addition, granzyme A/ B-deficient animals were shown to retain potent in vivo antitumor activity, suggesting that these granzymes are not required for tumor clearance.…”
Section: Lessons From Granzyme-deficient Animalsmentioning
confidence: 99%
“…The only alteration in cell-mediated immunity was a partially impaired response to MCMV. 85 GrM functions outside of direct killing have also been proposed, as GrM proteolytically inactives a GrB endogenous inhibitor, PI9. 86 The investigators proposed a model wherein GrM could assist GrB-induced killing by relieving PI9 inhibition of GrB.…”
Section: Mechanisms Of Cytotoxicity and Physiological Roles Of Grsmentioning
confidence: 99%